Preferred home equity release approach for retirement - Ho, Tin Long; Bateman, Hazel; Hanewald, Katja (My University, 2022)
This paper investigates the preferred home equity release approach for retirement, given available options (downsizing, the government-offered Pension Loans Scheme, commercial reverse mortgages, and home reversion–type schemes) and reflecting current tax, superannuation, and age pension rules in Australia. We use state-of-the-art economic and actuarial modeling to identify the preferred approach for the use of housing wealth by Australian retiree households with different marital status, wealth portfolios, and preferences. The Pension Loans Scheme is found to be most beneficial if households only need to boost retirement income by a limited amount. Private reverse mortgages are more attractive if households prefer a large lump-sum at retirement age. Households with lower house price growth expectations should use home reversion schemes. When households have strong bequest motives, they should not downsize or use home equity release. Our results can help policymakers, financial advisers, and individuals to improve retirement outcomes.
Keywords: Ageing; Housing, communities and neighbourhoods; Income, wealth and finances